Slow violence and the environmentalism of the poor - Nixon, Rob, 1954- (Harvard University Press, 2011)
The violence wrought by climate change, toxic drift, deforestation, oil spills, and the environmental aftermath of war takes place gradually and often invisibly. Using the innovative concept of "slow violence" to describe these threats, the author focuses on the inattention we have paid to the attritional lethality of many environmental crises, in contrast with the sensational, spectacle driven messaging that impels public activism today. Slow violence, because it is so readily ignored by a hard charging capitalism, exacerbates the vulnerability of ecosystems and of people who are poor, disempowered, and often involuntarily displaced, while fueling social conflicts that arise from desperation as life sustaining conditions erode. In this book the author examines a cluster of writer/activists affiliated with the environmentalism of the poor in the global South. By approaching environmental justice literature from this transnational perspective, he exposes the limitations of the national and local frames that dominate environmental writing. And by illuminating the strategies these writer/activists deploy to give dramatic visibility to environmental emergencies, he invites his readers to engage with some of the most pressing challenges of our time.